STUDI PERBANDINGAN ANTARA “SONGKET BALAPAK DENGAN SONGKET BATABUA” - Albert Taourisia; Minarsih .; Syafril . (Universitas Negeri Padang, 2012)
Abstract This research is proposed to describe: (1) Describing the placement of motif which is implemented to the songket balapak and songket batabua. (2) Describing repetition technique which is used in songket balapak and songket batabua. (3) Describing structure material which is used in songket balapak and songket batabua. The data of this research was collected from each area, Pandai Sikek and Silungkang. The resource of this research is from the data documentation from the informant. The technique of data collection of this research was from focused interview and documentation. Research findings are, first, motif placement on Songket Balapak and Batabua is located into three parts, head, body and edge. Second, repetition technique that is done on both Songket is horizontal and vertical pattern repetition. Third, both of Songket use golden line, yet Songket Pandai Singkek use more golden line. Kata Kunci: Songket, Balapak, Batabua, Silungkang dan Pandai Sikek